Kinerja Pegawai Ditinjau dari Kualitas Kepemimpinan, Disiplin dan Lingkungan Kerja: Studi Kasus dada Kantor Kementerian Agama Kabupaten Boyolali - Nugroho, Ivan Setyo; Istiatin, Istiatin; Hartono, Sri (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The purpose of this research is to analyze the relationship between the quality of management, workplace discipline, and staff productivity at the Boyolali Regency Ministry of Religion. Quantitative description is used in this kind of study. Employees at the Kantor Kementerian Agama in Kabupaten Boyolali were polled using a questionnaire. Employees of the Kantor Kementerian Agama Kabupaten Boyolali were the subjects of this investigation. This study has a sample size of 44 people. Saturated sampling is being used. Classical tests of assumptions, multiple linear regression tests, hypothesis testing, and the coefficient of determination are all examples of methods that may be used to analyze data. Processing is done using IDM SPSS Statistics 26. This study found that three variables had a positive and statistically significant effect on employee output: leadership quality, disciplinary measures, and the physical setting of the workplace. Keywords: Employee Performance, Leadership Quality, Discipline, Work Environment